2019
DOI: 10.1097/aog.0000000000003517
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Machine Learning Algorithm for Predicting Response to Anticholinergic Medications for Overactive Bladder Syndrome

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…However, as more time persists, factors such as the number of drinks, and the volume of alcohol and water consumed become more useful as determinants in predicting the next urination. This study’s findings suggest that factors such as a child’s bladder size or an older adult’s UI can significantly impact the prediction of the next urination, which is consistent with previous research [ 6 , 7 , 24 ]. These results are in line with the literature finding that age can affect how much and how long a person can hold their urine [ 4 , 6 , 7 , 23 , 24 ].…”
Section: Conclusion Limitations and Future Worksupporting
confidence: 92%
“…However, as more time persists, factors such as the number of drinks, and the volume of alcohol and water consumed become more useful as determinants in predicting the next urination. This study’s findings suggest that factors such as a child’s bladder size or an older adult’s UI can significantly impact the prediction of the next urination, which is consistent with previous research [ 6 , 7 , 24 ]. These results are in line with the literature finding that age can affect how much and how long a person can hold their urine [ 4 , 6 , 7 , 23 , 24 ].…”
Section: Conclusion Limitations and Future Worksupporting
confidence: 92%
“…The scoping review identified many studies that developed or validated models to predict therapeutic response for which prevention of ADEs in patients not expected to benefit from treatment was stated as a motivation for model development. 18 (27%) of 67 studies addressed this use case [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and focused on antineoplastics to treat patients with cancer (four [22%] of 18 studies), or antivirals with or without immuno modulators to treat patients with HIV or hepatitis C (five [28%]). Eight (44%) of 18 studies evaluated a single AI model.…”
Section: Reviewmentioning
confidence: 99%
“…[31][32][33][34][35][36] Machine learning tools have also been deployed to predict the presence or absence of sperm in testicular biopsy in patients with nonobstructive azoospermia, pregnancy loss after vitro fertilization-embryo transfer, the response of patients with overactive bladder syndrome to anticholinergic medications, and disease recurrence in women with early-stage endometrial or cervical cancer. [37][38][39][40][41] Though promising, these models have not yet been deployed clinically.…”
Section: Clinical Applications Of Machine Learning In Obstetrics and ...mentioning
confidence: 99%